Dual SMO/BRAF Inhibition by Flavonolignans from Silybum marianum † - Diukendjieva, Antonia; Zaharieva, Maya M; Mori, Mattia; Alov, Petko; Tsakovska, Ivanka; Pencheva, Tania; Najdenski, Hristo; Křen, Vladimír; Felici, Chiara; Bufalieri, Francesca; Di Marcotullio, Lucia; Botta, Bruno; et al. (Antioxidants (Basel, Switzerland), 2020)
Silymarin is the standardized extract from the fruits of Silybum marianum (L.) Gaertn., a well-known hepatoprotectant and antioxidant. Recently, bioactive compounds of silymarin, i.e., silybins and their 2,3-dehydro derivatives, have been shown to exert anticancer activities, yet with unclear mechanisms. This study combines in silico and in vitro methods to reveal the potential interactions of optically pure silybins and dehydrosilybins with novel protein targets. The shape and chemical similarity with approved drugs were evaluated in silico, and the potential for interaction with the Hedgehog pathway receptor Smoothened (SMO) and BRAF kinase was confirmed by molecular docking. In vitro studies on SMO and BRAF V600E kinase activity and in BRAF V600E A-375 human melanoma cell lines were further performed to examine their effects on these proteins and cancer cell lines and to corroborate computational predictions. Our in silico results direct to new potential targets of silymarin constituents as dual inhibitors of BRAF and SMO, two major targets in anticancer therapy. The experimental studies confirm that BRAF kinase and SMO may be involved in mechanisms of anticancer activities, demonstrating dose-dependent profiles, with dehydrosilybins showing stronger effects than silybins. The results of this work outline the dual SMO/BRAF effect of flavonolignans from Silybum marianum with potential clinical significance. Our approach can be applied to other natural products to reveal their potential targets and mechanism of action.
Keywords: silybins; Smoothened; in silico methods; cytotoxicity; BRAF kinase